Framing post-disaster collective action as 'good news': Possibilities and tensions. (April 2023) - Carlton, Sally; Nissen, Sylvia; Wong, Jennifer HK
This article examines the development and implications of positive news media coverage of a crisis volunteer group across a decade of disaster responses. We investigate the case of the Student Volunteer Army in Aotearoa New Zealand, a group that has been positioned as a potential blueprint for youth-led disaster response. Drawing on in-depth interviews and news media sources, we trace how a distinct framing of the group as 'good news' consolidated across successive disasters, initially in media reporting and then through active cultivation by the group. The findings demonstrate the potential for positive media coverage of disaster volunteerism to assist people's recovery and provide crisis volunteer groups with important leverage to further their operational abilities and challenge exclusionary power structures in post-disaster environments. However, our analysis also warns that simplifying accounts of post-disaster collective action to create 'good news' can produce internal tensions within crisis volunteer groups and reinforce the hierarchies and inequities that characterize disaster response.